2023
DOI: 10.1002/bmm2.12040
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of zinc oxide nanorod arrays on breast cancer cells profiled through real‐time cytokines screening by a single‐cell microfluidic platform

Ping Li,
Chao Wang,
Jiaoyan Qiu
et al.

Abstract: Zinc oxide nanorods have been extensively studied for the specific killing of breast cancer (BC) cells, and their killing mechanism and anticancer effects have been initially demonstrated. However, systematic studies at the single‐cell level are still necessary to explore cellular functions in detail. In this work, a hydrothermal method was used to synthesize zinc oxide nanorod arrays (ZnO NRs). Their effect on BC cells was demonstrated at single‐cell resolution for the first time through microfluidic chips an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Changes in cell function under the influence of external conditions can be well explained through omics analysis. [38] This study investigated the influence of FSS and HP on the mechanical transduction pathways of BMSCs through transcriptomics. Consequently, it becomes feasible to discern the distinctions in the mechanisms of FSS and HP in inducing osteogenic differentiation of BMSCs, thus providing insights into potential crosstalk.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in cell function under the influence of external conditions can be well explained through omics analysis. [38] This study investigated the influence of FSS and HP on the mechanical transduction pathways of BMSCs through transcriptomics. Consequently, it becomes feasible to discern the distinctions in the mechanisms of FSS and HP in inducing osteogenic differentiation of BMSCs, thus providing insights into potential crosstalk.…”
Section: Discussionmentioning
confidence: 99%
“…Thousands of single cells were cultured and analyzed in situ on this chip developed by our team, revealing the impact of nanomaterials and external force stimulation on the growth and differentiation of single cells during the culture process. [ 43 , 44 , 45 ] A Microchamer chip was also used to study the grouping mechanism of single cells, enabling cancer cell subtype diagnosis and evaluation of immune cell efficacy. [ 37 , 46 , 47 ]…”
Section: Single‐cell Isolation Chip Technologymentioning
confidence: 99%
“…Studies have shown that delivering cells or drugs without carriers can result in significant leakage from the injection site, , and carriers are therefore needed to avoid this . Several new biomaterials are gaining attention for their promising results in biomedicine. Hydrogels have favorable cytocompatibility, and their internal porous structure facilitates cell adhesion and growth by providing space for cells to grow inward . Hydrogels are also considered to have the potential to surpass conventional materials because they can integrate with various drugs and cells .…”
Section: Introductionmentioning
confidence: 99%